From Dichotomies to Dialogues Connecting Discourses for a Sustainable Urbanism - van Dorst, Machiel; Qu, Lei (TU Delft Open, 2023)
Urbanism is a way of thinking and acting needed for sustainable development; urbanists are becoming inter- and transdisciplinary, bringing science, technology, and design into their field. As the world is in a cascading of crises related to, e.g., health, energy, food, and water, as well as issues of, e.g., traffic, housing, and services, integrated approaches become increasingly relevant as most of these challenges are related. Having a holistic urbanism viewpoint is the path to resilience and sustainability. Here, we are not referring to a longer list of notions but particularly encouraging dialogues between (possibly perceived) conflicting discourses. This book is the proceedings of the 14th IFoU conference, a stepping stone towards a new culture of working together. It includes papers in five tracks representing five types of debates over a set of dichotomies: 1 "Urban-rural Integration" and "Areas In-Between" 2 The City is an Object and a City is in Transition 3 Political Ecology and Adaptive and Transformative Framework 4 Metropolization and the Right to the City 5 Human-centred and Nature-based Approaches in Cities